2022
DOI: 10.3390/f13091345
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intercropping between Morus alba and Nitrogen Fixing Species on Soil Microbial Community Structure and Diversity

Abstract: The intercropping of nitrogen-fixing and non-nitrogen-fixing tree species changed the availability of soil nitrogen and soil microbial community structure and then affected the regulation process of soil carbon and nitrogen cycle by microorganisms in an artificial forest. However, there is no consensus on the effect of soil nitrogen on soil microorganisms. In this study, the intercropping of mulberry and twigs was completed through pot experiments. Total carbon, total nitrogen, and total phosphorus in the rhiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…For example, mulberry/alfalfa intercropping increases the richness and diversity of bacterial community by affecting the content of soil total carbon, available potassium, and phosphate ( Zhang et al, 2018 ). Morus alba/Lespedeza bicolor intercropping significantly elevates the evenness and diversity of fungal community by affecting the contents of soil total carbon, nitrogen, and phosphate ( Liu J. et al, 2022 ). Correspondingly, our results also observed that maize/peanut intercropping system can significantly increase bacterial richness.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mulberry/alfalfa intercropping increases the richness and diversity of bacterial community by affecting the content of soil total carbon, available potassium, and phosphate ( Zhang et al, 2018 ). Morus alba/Lespedeza bicolor intercropping significantly elevates the evenness and diversity of fungal community by affecting the contents of soil total carbon, nitrogen, and phosphate ( Liu J. et al, 2022 ). Correspondingly, our results also observed that maize/peanut intercropping system can significantly increase bacterial richness.…”
Section: Discussionmentioning
confidence: 99%
“…Using fasttree2 and mafft, non-singleton amplicon sequence variants (ASVs) were used to create a phylogenetic tree ( Katoh, 2002 ; Price et al, 2009 ). Alpha-diversity metrics [Observed species richness ( Liu et al, 2022 ), Simpson index ( Simpson, 1949 ), and Pielou’s evenness index ( Pielou, 1966 )], beta diversity metrics (Bray-Curtis dissimilarity) were estimated using the diversity plugin. The SILVA Release 132 Database (Bacterium) and UNITE Release 8.0 Database (Fungus) were used as the sources for the naive Bayes taxonomy classifier in the feature-classifier plugin to assign taxonomy to ASVs ( Kõljalg et al, 2013 ; Bokulich et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…The sample was kept in a 100 mL volume bottle after digestion and cooling. The molybdenum-antimony resistance colorimetric method was used to perform colorimetric analysis on five mL of filtrate using a spectrophotometer (P4 UV-Visible China) and a 50 mL volumetric bottle ( Liu et al, 2022b ).…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, it has a substantial influence on soil microbial community diversity and building processes ( Cheng et al, 2021 ). It has been shown that land use type explained 97% of the variability in soil quality indices and that different vegetation measures had significant effects on vegetation composition and structure, biomass, litter, soil moisture, soil nutrients and soil microorganisms of the ecosystem ( Xu et al, 2014 ; Zhang et al, 2011 ; Liu et al, 2022a ; Liu et al, 2022b ). Changes in vegetation type not only alter the landscape appearance of the land, but also the material cycle and energy flow of the soil ecosystem, while having a profound impact on the structure and function of soil microorganisms ( Wan & He, 2020 ; Zhang et al, 2013 ; Tian et al, 2017 ; Delgado-Baquerizo et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%